Numerical Study on the Sagging Damage of the Simplified Hull Girder Subjected to Underwater Explosion Bubble - Yuxiang Gong; Wenpeng Zhang; Zhipeng Du; Yinghao Zhu (Applied Sciences, 2023)
The pulsation of the bubbles resulting from underwater explosions can lead to severe damage to the structure of the ship’s hull, and even to its sinking. To study the damage mechanism of a simplified hull girder (SHG) subjected to near-field underwater explosion bubble, the Coupled Eulerian–Lagrangian (CEL) method based on verifications of the calculation accuracy was used to simulate 11 SHG structures. The sagging bend mechanism of SHGs was analyzed from the perspective of plastic hinge lines. Moreover, the length formula of the potential bend zone was studied through the assumed plastic hinge lines. The influence of transverse bulkheads on bending mode and total longitudinal strength was investigated. The results show that SHGs’ sagging damage is composed of regular plastic hinge lines, mainly depending on side plates’ folding—W-shaped in this paper. When facing the near-field underwater explosion bubble, the distant transverse bulkheads influence the total longitudinal strength and do not always play a positive role.